Rhipidocotyle labroidei n. sp. (Digenea: Bucephalidae) from Labroides dimidiatus (Valenciennes) (Labridae) - Jones, Conor M.; Grutter, Alexandra S.; Cribb, Thomas H. (Zootaxa, 2003)
Rhipidocotyle labroidei n. sp. is described from the rectum of cleaner fish, Labroides dimidiatus (Labridae), on the Great Barrier Reef. R. labroidei differs from its congeners by the combination of its small size, anteriorly directed caecum, the shape and positioning of its gonads, and by its posteriorly confined uterus. We have found Rhipidocotyle in species of Labroides from New Caledonia and Moorea that differ from the described material in the size of eggs, but these worms are not suitable for description. We suggest there are at least two species of Rhipidocotyle in Labroides spp. from the tropical Pacific.